Aldehyde dehydrogenase-1 positivity is associated with ER negativity in patients with invasive ductal carcinoma of the breast - Köy, Yazgı; Dirilenoglu, Fikret; Tetikkurt, Ümit; Muhammedoğlu, Ali; Çelik, Atilla (Polish Journal of Pathology, 2020)
Cancer stem cells (CSCs) are self-renewable and can be differentiated into different cell types. They play an important role in oncogenic signaling pathways, tumor cell heterogeneity, metastasis, and therapeutic resistance. Aldehyde dehydrogenase 1 (ALDH1) was identified as a specific marker for breast CSCs. The study included a total of 105 patients with a diagnosis of invasive ductal carcinoma (IDC) who underwent mastectomy and with sufficient pathology material for histopathological examination. Patient demographics, tumor location, tumor diameter, the presence of lymphovascular and perineural invasion and lymph node metastasis, surgical margin status, and immunohistochemistry (IHC) staining results were obtained from patients’ records. The tumors were classified into IHC-based molecular subtypes according to the St. Gallen Consensus Conference in 2013. A four-tiered scoring system was used based on ALDH1 staining percentage in tumor cells. The tumor was determined as positive if the score was 2 or higher. Clinical, histopathological findings, and ALDH1 staining results were correlated. Twenty-five cases (23.8%) were ALDH1 positive. The ALDH1 positive group compared to the negative group was found to be associated with ER negativity (p = 0.044), but there was no correlation with other clinical and histopathological findings. ALDH1-positive IDCs may be less sensitive to hormonal therapy and associated with aggressive behavior.